ANALYSIS OF INPUT TEAM COMPOSITION (HOCH MODEL) AT THE FACULTY OF ECONOMICS AND BUSINESS RIAU UNIVERSITY ON THE DIGITAL AGE - Rizky Mardianto; Raden Lestari Garnasih; Marzolina Marzolina (Universitas Kristen Indonesia Toraja, 2022)
The purpose of this study was to determine the input analysis of Team Composition (HOCH MODEL) Lecturer of the Faculty of Economics and Business, University of Riau. Primary data wa s collected through a questionnaire as a tool to prove the results of the study, the dat analysis technique in this study used SPSS, the sampling technique that has been selected is the Descriptive Analysis method (82 Lecturer of the Faculty of Economics and Business, Riau University). The results show that: 1) Surface Level Diversity at the Faculty of Economics and Business, Riau University is very good with E-learning 2) Deep Level Diversity at the Lecturer at the Faculty of Economics and Business, Riau University agrees that Deep Level Diversity can lead to good things in the Team Composition 3) Knowledge, Skills, Ability at the Lecturer of the Faculty of Economics and Business, University of Riau agrees that Knowledge, Skills, Ability are very important when carrying out Elearning learning 4) Other Individual Diferences at the Lecturer of the Faculty of Economics and Business, University of Riau agrees that Other Individual Diferences are very important important to do in a team in carrying out E-learning learning